Antibacterial activity of endosymbiotic bacterial compound from Pheretima sp. earthworms inhibit the growth of Salmonella Typhi and Staphylococcus aureus: in vitro and in silico approach - Dirayah Rauf Husain (Iranian Journal of Microbiology, 2021)
Background and Objectives: Earthworms coexist with various pathogenic microorganisms; thus, their immunity mechanisms have developed through a long process of adaptation, including through endogenous bacterial symbionts. This study aims to identify earthworm endosymbiont bacteria compounds and their antibacterial activity through an in vitro approach supported by an in silico approach. Materials and Methods: This research was conducted using the in vitro inhibition test through agar diffusion and the in silico test using molecular docking applications, namely, PyRx and Way2Drugs Prediction of Activity Spectra for Substances (PASS). Results: The in vitro results showed a potent inhibition activity with a clear zone diameter of 21.75 and 15.5 mm for Staphylococcus aureus and Salmonella Typhi, respectively. These results are supported by chromatography and in silico tests, which showed that several compounds in endosymbiotic bacteria, cyclo (phenylalanyl-prolyl) and sedanolide, have high binding affinity values with several antibiotic-related target proteins in both pathogenic bacteria. Cyclo (phenylalanyl-prolyl) has the highest binding affinity of -6.0 to dihydropteroate synthase, -8.2 to topoisomerase, and -8.2 to the outer membrane, whereas sedanolide has the highest binding affinity to DNA gyrase with approximately -7.3. This antibiotic activity was also clarified through the Way2Drugs PASS application. Conclusion: Ten active compounds of endosymbiont bacteria, Cyclo (phenylalanyl-prolyl) and sedanolide were potential candidates for antibacterial compounds based on the inhibition test of the agar diffusion method and the results of reverse docking and Way2Drugs PASS.